Решить поcледовательно, а не просто ответ.

19sin2x + 6cos^2x - 12 = 0;

9cosx + sinx - 1 = 0;

1

Ответы и объяснения

  • Участник Знаний
2013-04-07T20:16:05+04:00

19sin2x + 6cos^2x - 12 = 0

19*2sinxcosx+6cos^2x - 12(cos^2x+sin^2x) = 0

-12sin^2x+38sinxcosx-6cos^2x=0   /:(-2)

6sin^2x-19sinxcosx+3cos^2x=0  /:cos^2x≠0

6tg^2x-19tgx+3=0

tgx=t

6t^2-19t+3=0

D=289

t=3

t=1/6

 

x=arctg(3)+pik, k∈Z

x=arctg(1/6)+pik, k∈Z

 

 

9cosx + sinx - 1 = 0

подстановка tg(x/2)=t

9*(1-t^2)/(1+t^2)+2t/(1+t^2)-1=0

9*(1-t^2)+2t-(1+t^2)=0

9-9t^2+2t-1-t^2=0

-10t^2+2t+8=0    /:(-2)

5t^2-t-4=0

D=1+16*5=81

t=(1+9)/10=1

t=(1-9)/10=-8/10=-4/5

 

tg(x/2)=1

x/2=pi/4+pik     /*2

x=pi/2+2pik

 

tg(x/2)=-4/5

x/2=-arctg(4/5)+pik

x=-2arctg(4/5)+2pik